Production of biodiesel using high free fatty acid feedstocks - Atadashi, I.M.; Aroua, Mohamed Kheireddine; Abdul Raman, Abdul Aziz; Sulaiman, N.M.N. (Elsevier, 2012)
The enormous challenges faced in the search for suitable and profitable feedstocks to produce biodiesel cannot be over-emphasis. This paper has provided an overview of different catalysts used in processing different kinds of feedstocks for the production of biodiesel. Although the process of biodiesel production from refined feedstocks is less cumbersome and could provide biodiesel yield of more than 98, but its product cost is high. Thus, the recent biodiesel production from low-quality feedstocks, though presents challenges but has equally provided biodiesel yield comparable to that obtained from refined feedstocks. Furthermore the physicochemical properties of biodiesel derived from low-quality feedstocks are discussed. Additionally economic evaluation of biodiesel from low-quality feedstocks is examined. The result showed that if less expensive feedstocks are used to produce biodiesel, a 25 reduction in cost production is possible. Thus making biodiesel price reasonably closed to the price of petro-diesel. (C) 2012 Elsevier Ltd. All rights reserved.